2008
DOI: 10.1063/1.2832630
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of charge distribution in crystalline and amorphous Si nanoclusters in thin silica films

Abstract: Crystalline and amorphous nanoparticles of silicon in thin silica layers were examined by transmission electron microscopy, electron energy loss spectroscopy, and x-ray photoelectron spectroscopy ͑XPS͒. We used XPS data in the form of the Auger parameter to separate initial and final state contributions to the Si 2p energy shift. The electrostatic charging and electron screening issues as well as initial state effects were also addressed. We show that the chemical shift in the nanocrystals is determined by ini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 48 publications
4
39
0
Order By: Relevance
“…This value fits well with the reported binding energy of 135.3 eV for P 4 O 10 . 16 It should be mentioned here that at this depth (4-11 nm), the O(P 3 ) peak of the O1s was observed which was assigned to P 4 17 In the present work, the energy separation between the peak P-2p 3=2 and Si-2p 3=2 is used to monitor the relative positions of the two peaks with depth. An increase of the P-2p 3=2 -Si-2p 3=2 energy separation implies either a reduced screening of the P-2p 3=2 and/or an increased screening of the Si-2p 3=2 .…”
Section: Resultsmentioning
confidence: 68%
“…This value fits well with the reported binding energy of 135.3 eV for P 4 O 10 . 16 It should be mentioned here that at this depth (4-11 nm), the O(P 3 ) peak of the O1s was observed which was assigned to P 4 17 In the present work, the energy separation between the peak P-2p 3=2 and Si-2p 3=2 is used to monitor the relative positions of the two peaks with depth. An increase of the P-2p 3=2 -Si-2p 3=2 energy separation implies either a reduced screening of the P-2p 3=2 and/or an increased screening of the Si-2p 3=2 .…”
Section: Resultsmentioning
confidence: 68%
“…[11,24], and the concentration of which can be further reduced by increasing both the annealing time and temperature [13]. Secondly, the binding-energy difference (chemical shift) between Si 0 and the Si 4+ peaks increases, from 3.6 eV (as-deposited) to 4.3 eV (annealed at 1000 1C), most probably due to the better phase separation and, more importantly, enhanced differential charging [25]. To clarify the reaction detail of the decomposition reactions of the Si suboxides in SiO x during annealing, the changes of the concentrations of the five oxidation states with annealing have been examined quantitatively.…”
Section: Article In Pressmentioning
confidence: 97%
“…Recently, Thogersen et al have shown that the amount of the shift is different for amorphous and crystalline phases, as well as varies with the size of the Si nanoclusters. They analyzed a set of samples with various fabrication and postannealing treatments using initial and final state Auger parameters, and Wagner diagram [49]. The authors designated that the shift is ruled by initial state rather than final state.…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 99%